ENVIRONMENTAL ANALYSIS ON SOFT CLAY SOIL STABILIZATION AS A SUBGRADE IN BINJAI – PANGKALAN BRANDAN TOLL ROAD PROJECT - I Made Kusuma Wiranata; I Nengah Sinarta; Putu Ika Wahyuni (Master Program of Infrastructure and Environmental Engineering, Postgraduate Program, Warmadewa University, 2024)
Soft soil poses significant challenges in road construction projects, particularly in the Binjai - Pangkalan Brandan Toll Road, where non-uniform settlement of landfills has been observed. To address these issues and achieve the desired subgrade quality and compression, various soft soil stabilization methods have been employed, including mechanical approaches such as Prefabricated Vertical Drain (PVD) with preloading or vacuum and Pile Embankment. This study aims to evaluate the environmental impact of these three stabilization methods using the Strength, Weakness, Opportunities, and Threats (SWOT) method. Primary data was collected through interviews with experts from diverse stakeholders, including academics, planning consultants, and implementing contractors, using the purposive sampling technique. Focus Group Discussion (FGD) was conducted to develop SWOT strategies for each repair method based on environmental assessment indicators derived from literature studies. The SWOT analysis results indicate that the PVD Preloading method is the most environmentally friendly among the three methods. This is attributed to the absence of cement usage, lower electrical energy consumption, and the use of more environmentally friendly materials. Although PVD Preloading requires additional backfill for the preloading process, the impact on the environment is minimal, as the soil material used comes from the project site, and approximately 90% of the backfill is returned as road backfill after the consolidation process is complete. The analysis also reveals that the speed of the consolidation process is inversely proportional to its environmental friendliness.